Determination of illness cognition levels in patients with maxillofacial area defects - Lamia Najafova; Hilal Eksi Ozsoy; Huseyin Kurtulmus (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
The aim of this study was to measure the illness cognition of patients with defect in the maxillofacial region. Eighty patients participated in this study. Written informed consent was obtained from patients with maxillofacial area defect, and the patients were filled in with the guidance of the researchers. Illness Cognition Questionnaire (ICQ), forms measuring the illness awareness of the patients were completed.  The study was conducted independently of demographic characteristics. The statistical software SPSS (Statistical Package for Social Sciences, Version 20, Chicago IL, USA) was used for calculations. At the end of the study, ICQ scores in patients with maxillofacial defect were as follows: There was a statistically significant intra class correlation of 88.6% (0.843-0.942) among the Helplessness scale scores of the participants. There was a statistically significant intra class correlation of 80.3% (0.728-0.863) among the Acceptance scale scores of the participants. There was a statistically significant intra class correlation of 0.752 % (0,657-0,827) among the Perceived benefits scale scores of the participants. Patients with maxillofacial defects will focus on the disease cognition "Helplessness" category. In patients with relationship maxillofacial defect, the rate of helplessness (88.6%) was higher than acceptance (80.3%) and perceived benefit (0,752 %).